Discourse Construction on the Appointment of SPPG Employees to PPPK in Online Media Reporting: A Critical Discourse Analysis of Teun A. van Dijk's Model - Ramdan Gumilar; Deasy Aditya Damayanti; Ninah Hasanah; Agus Ha; Ari Kartini (Journal of Innovation and Research in Primary Education, 2026)
Online media plays a crucial role in conveying and explaining public policy to the public. This study aims to examine how Liputan6.com presents the discourse on the appointment of Nutrition Fulfillment Service Unit (SPPG) employees to Government Employees with Work Agreements (PPPK) in the Free Nutritional Meal Program (MBG). This study uses a descriptive qualitative approach with Teun A. van Dijk's Critical Discourse Analysis method, which includes analysis of text structure, social cognition, and social context. The research data consists of a Liputan6.com news text entitled "The Uproar Over SPPG Employees Being Appointed as PPPK, Here's the BGN's Explanation" published in January 2026. The results show that in the text dimension, the news placed the official clarification from the National Nutrition Agency (BGN) as the main focus through informative and explanatory news structures and language choices. In the social cognition dimension, the media presented the government's institutional perspective as the primary reference in understanding the policy. Meanwhile, in the social context, the news served to clarify the regulatory boundaries between state officials and volunteers. This study concludes that online media plays a role as a mediator of policy information that contributes to building public understanding in a targeted and contextual manner.